MAGEL2 (patho-)physiology and Schaaf-Yang syndrome - Schubert, Tim Felix; Schaaf, Christian P. (Developmental medicine and child neurology, 2025)
Schaaf-Yang syndrome (SYS) is a complex neurodevelopmental disorder characterized by autism spectrum disorder, joint contractures, and profound hypothalamic dysfunction. SYS is caused by variants in MAGEL2, a gene within the Prader-Willi syndrome (PWS) locus on chromosome 15. In this review, we consolidate decades of research on MAGEL2 to elucidate its physiological functions. Moreover, we synthesize current knowledge on SYS, suggesting that while MAGEL2 loss-of-function seems to underlie several SYS and PWS phenotypes, additional pathomechanisms probably contribute to the distinct and severe phenotype observed in SYS. In addition, we highlight recent therapeutic advances and identify promising avenues for future investigation.